Modelling charge storage near full well in CCDs. (17th May 2017) - Weatherill, D.P.; Plackett, R.; Arndt, K.; Shipsey, I.P.J.
Abstract: The shape and size of the stored charge packet within a CCD pixel after exposure has implications for optimal device operation, susceptibility to radiation damage and modelling of dynamic charge collection effects such as the "Brighter-Fatter Effect". Above the full well capacity, phenomena such as bleed trails and surface charge loss occur. In this paper we discuss why accurately reproducing saturation effects in simulations based on electrostatics is difficult, and present an approach to modelling the storage of charge in CCD pixels using commercial semiconductor simulation software. We suggest experimental measurements which can be connected to such modelling. Full well measurements on a thick, high resistivity back illuminated sensor (the e2v CCD261) are presented.